Employee Perceptions towards the Effectiveness of the Whistleblowing System Research - Ririn Breliastiti; Temy Setiawan; Tiwi Herninta; Nasya Lita Natalsya (International Journal of Multidisciplinary Sciences and Arts, 2025)
Recent high-profile corporate scandals, such as Enron, Volkswagen, and Lehman Brothers, underscore the critical role of whistleblowing systems (WBS) in uncovering fraud and unethical practices. Despite their importance, challenges persist in implementation, including employee fears of retaliation and inconsistent follow-up. This study examines employee perceptions of WBS effectiveness, aiming to: (1) evaluate WBS efficacy in whistleblower protection, report handling, and sanctions; (2) analyze cultural acceptance and challenges; (3) identify factors influencing employee comfort (e.g., anonymity, trust in management); and (4) propose recommendations for improvement. Using qualitative methods, data were collected via online interviews with 36 employees (18 meeting criteria) from Indonesian companies, primarily in finance, and analyzed thematically using NVivo software. Results revealed that while WBS enhances transparency and enables faster detection of major violations (e.g., corruption), effectiveness is hampered by insufficient follow-up on minor cases, technical barriers (e.g., email server issues), and fears of social retaliation. Employee comfort hinges on robust anonymity guarantees and transparent processes, yet 61% of respondents expressed uncertainty about protection mechanisms. Corporate culture generally supported WBS but risked misuse in hierarchical or small-team environments. Recommendations include strengthening policy socialization, ensuring impartial sanctions, upgrading technical infrastructure, and enforcing strict confidentiality. The study concludes that WBS effectiveness requires organizational commitment to cultural and procedural reforms, though limitations in sample diversity and subjective data necessitate future mixed-method research across broader sectors and direct observation of WBS implementation.